Effects of high-intensity exercises on 13C-Nandrolone excretion in trained athletes - Baume, N.; Avois, L.; Sottas, P. -E.; Dvorak, J.; Cauderay, M.; Mangin, P.; Saugy, M. (Clinical Journal of Sport Medicine, 2005)
Objective: Nandrolone is an anabolic steroid widely used in several sports. The numerous nandrolone positive cases in the recent years (International Olympic Committee statistics) led to several studies in the antidoping field. Nevertheless, essential questions pertaining to nandrolone endogenous production, the effects of physical exercise on the excretion of nandrolone metabolites, and contamination from nutritional supplements must still be addressed. The purpose of this study was to evaluate the influence of exhaustive exercises on 19-norandrosterone (19-NA) and 19-noretiocholanolone (19-NE) urinary excretion rates after administration of labeled nandrolone.